Procedural Considerations in Piercing the Corporate Veil: A Survey of Jurisprudence - Alonzo, Kent A.; Marella, Jose Maria L. (Diliman, Quezon City, Philippines: University of the Philippines College of Law)
I. Jurisprudence: 2010 to 2016; II. Synthesizing the Rules and Jurisprudence; III. Conclusion.